2011
DOI: 10.1177/1745691611400236
|View full text |Cite
|
Sign up to set email alerts
|

Can Sex Differences in Science Be Tied to the Long Reach of Prenatal Hormones? Brain Organization Theory, Digit Ratio (2D/4D), and Sex Differences in Preferences and Cognition

Abstract: Brain organization theory posits a cascade of physiological and behavioral changes initiated and shaped by prenatal hormones. Recently, this theory has been associated with outcomes including gendered toy preference, 2D/4D digit ratio, personality characteristics, sexual orientation, and cognitive profile (spatial, verbal, and mathematical abilities). We examine the evidence for this claim, focusing on 2D/4D and its putative role as a biomarker for organizational features that influence cognitive abilities/int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 53 publications
1
42
2
Order By: Relevance
“…2b are also consistent with a nonlinear relationship of 2D:4D to both FIE and t:e. Indeed, quadratic functions did modestly improve the amount of variance accounted for, and some previous results in the literature are consistent with a U-shaped relationship between 2D:4D and cognition (Brosnan, 2006;Falter, Arroyo, & Davis, 2006). Note, however, that this issue is distinct from proposals elsewhere that prenatal androgen may relate nonmonotonically to cognition (Brosnan, 2006;Geschwind & Galaburda, 1987;Valla & Ceci, 2011); the firm implication Fig. 2 (a) Plots of each observer's 2D:4D, a marker for testosterone and estradiol exposure, against the magnitude of their face inversion effectcalculated as A', from overall P (Hit) and P(FA).…”
Section: Discussionmentioning
confidence: 42%
“…2b are also consistent with a nonlinear relationship of 2D:4D to both FIE and t:e. Indeed, quadratic functions did modestly improve the amount of variance accounted for, and some previous results in the literature are consistent with a U-shaped relationship between 2D:4D and cognition (Brosnan, 2006;Falter, Arroyo, & Davis, 2006). Note, however, that this issue is distinct from proposals elsewhere that prenatal androgen may relate nonmonotonically to cognition (Brosnan, 2006;Geschwind & Galaburda, 1987;Valla & Ceci, 2011); the firm implication Fig. 2 (a) Plots of each observer's 2D:4D, a marker for testosterone and estradiol exposure, against the magnitude of their face inversion effectcalculated as A', from overall P (Hit) and P(FA).…”
Section: Discussionmentioning
confidence: 42%
“…A possible mechanism behind this association is the influence of embryogenic sex hormone exposure on brain development (15,22). We speculate that higher androgen levels might influence the regulation and coping of pain stimuli by the brain, thereby increasing the susceptibility for developing chronic joint pain.…”
Section: Discussionmentioning
confidence: 99%
“…Like finger length pattern, embryogenic brain development is influenced by prenatal androgen exposure, specifically in the development of sex differences in the brain (15). Chronic pain is also sex associated; therefore, prenatal androgen exposure, as measured by finger length pattern, might be associated with the risk for chronic pain by this shared association with sex and thus androgens.…”
Section: Introductionmentioning
confidence: 99%
“…The gender gap has been narrowed in many societies and a recent study by Guiso et al (2008) found that the mathematics gender gap disappears in more gender-equal cultures. In the United States, Valla and Ceci (2011) found that in 1970, fewer than 5% of scientific and medical doctorates were awarded to women, but by 2006, the percentages of female doctorates in these fields exceeded 45%.…”
Section: Intoductionmentioning
confidence: 99%